Strategi Pengelolaan Ekowisata Mangrove Pulau Bangkobangkoang Kabupaten Pangkep, Sulawesi Selatan - Amal Arfan; Muhammad Faisal Juanda; Maddatuang .; Ramli Umar; Rosmini Maru; Anshari . (Jurnal Analisis Kebijakan Kehutanan, 2022)
Mangrove forest on Bangkobangkoang Island has the potential to be managed to become an ecotourism area. Such management requires a strategy to provide both economic and ecological benefits. The purpose of the study was to analyze the ecotourism management strategy of mangrove forests on Bangkobangkoang Island, Pangkep Regency, South Sulawesi. The sampling technique used is purposive. Data collection techniques are observations and surveys on mangrove forests, questionnaires, and interviews with island communities. The analysis technique used is SWOT. The results showed that the mangrove forest of Bangkobangkoang Island has a thickness of 230.39 m, a density of 23.25 ind/100m2, tides as high as 1.49 m, and there are 5 species of mangrove found and aquatic biota, birds, and others. The priority strategy is to maximize the potential of mangrove forests and preserve their naturalness so that they become a means of education to improve the community's economy, Coordination and communication between community members and the government in efforts to manage ecotourism areas, Empower fisherman groups in managing ecotourism, Procurement of supporting facilities for monitoring mangrove ecosystems, Training on product making made from mangroves to increase community income and maintain and strengthen community participation and interest in managing mangrove forests into ecotourism areas. This research can be input for stakeholders in making policies.